Technology Entrepreneurship Project : ENT (600) : Coway Co. Ltd. / Nur Syamimi Mohamad Abdul Adziz - Mohamad Abdul Adziz, Nur Syamimi (2021)
Coway Company is a company that known with their high technology of health and wellbeing products, which one of it is a water purifier. By doing this research, I got the opportunity to research a company that manufactured the same product as I wish to develop which is Coway Company that also produce a water purifier that currently based in Malaysia. From this case study, I can collect general information about the company such as the background of the company, technology used, their services, and learn about their business, marketing and operating strategy. Coway has many products such as water purifier, air purifier, mattress and bathroom. In this project, I would like to only focus on one product that I interested which water purifier as nowadays we are having a problem with water we used to drink every day. The product that I would like to develop is a Chitosan water filter with self-cleaning technology I have done SWOT analysis on the Coway Company which make me able to distinguish the strength, weakness, opportunities and threats of this company. Based on the SWOT analysis, there are two major problems identified which are filter use always have clogging issues that disturb water flow and water taste and also the water purifier need to be service frequent that take a lot of costs. This helps me to figure out a better technology system solution that can be implemented in the company to cope with the current issues. I suggested substituting the filter use with a filter made from Chitosan which has good criteria for trapping a contaminant and also has a high surface area. Other than that, I also suggested implementing self-cleaning technology which is a flushing system. The strategy and planning to improve the existing system are really important in business development growth. This will make the product more commercial and bring more benefit to others.